2019
DOI: 10.1177/000313481908501024
|View full text |Cite
|
Sign up to set email alerts
|

International Normalized Ratio (INR) is Comparable to MELD in Predicting Mortality after Cholecystectomy

Abstract: Guidelines suggest targeting a preoperative international normalized ratio (INR) < 1.5. We examined and compared the predictive value of INR relative to the Model for End-Stage Liver Disease (MELD). We reviewed the American College of Surgeons NSQIP from 2005 to 2016 for adult patients undergoing open or laparoscopic cholecystectomy. Patients with a preoperative INR were stratified into groups: ≤1, >1 to ≤1.5, >1.5 to ≤2, and >2. Thirty day postoperative mortality was the primary outcome. Multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…P reoperative elevated INR has been confirmed to increase bleeding, complications, and mortality in some other diseases [34][35][36][37][38][39][40] . Measuring INR before joint surgery was a standard pattern in our institution.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…P reoperative elevated INR has been confirmed to increase bleeding, complications, and mortality in some other diseases [34][35][36][37][38][39][40] . Measuring INR before joint surgery was a standard pattern in our institution.…”
Section: Discussionmentioning
confidence: 97%
“…The INR is widely used in predicting mortality and bleeding in some diseases. Rudasill et al found that the INR showed important value in predicting mortality and bleeding in end-stage liver disease 34 . Patients who underwent endarterectomy with high preoperative INR (≥1.5) exhibited higher 90-day mortality than low INR patients (<1.5) 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative elevated INR had been con rmed to increase bleeding, complication and mortality in some diseases [11][12][13][14][15][16][17]. Measuring INR before joint surgery was a standard pattern in our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Among the warfarin used patients, INR was kept between 2.0 and 3.0 as the therapeutic range [10]. A preoperative international normalized ratio (INR) target < 1.5 is suggested by the guidelines [11]. INR was widely used in predicting mortality and bleeding in some diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation